The effect of semolina replacement with protein powder from fish (Pseudophycis bachus) on the physicochemical characteristics of pasta. (March 2018) - Desai, Ajay; Brennan, Margaret A.; Brennan, Charles S.
Abstract: This study replaced semolina with red cod (Pseudophycis bachus) fish powder in pasta at 5, 10, 15 and 20 g/100 g levels. The effects on the chemical composition, physical properties (optimal cooking time, cooking loss, water absorption index, swelling index and colour) and textural properties (firmness and extensibility) of the supplemented pasta samples were evaluated compared with a control sample. Fortification with fish powder increased protein, lipid and ash contents significantly (P < 0.05). Cooking loss increased (P < 0.05) with increasing levels of fish powder. However, all pasta samples were in the acceptable range (8 g/100 g) for cooking loss. Fish powder incorporation decreased optimal cooking time, swelling index and water absorption significantly (P < 0.05), whilst increasing firmness and resistance to uniaxial extension of pasta. The addition of fish powder increased yellowness (b*) of the pasta significantly (P < 0.05) compared to control sample. Thus, pasta fortified with fish powder has the potential to be a technological alternative for the food industry to provide nutritional enriched pasta. Highlights: Nutricious pasta was produced by adding fish powder to semolina. Replacing semolina with fish powder showed high protein contents of pasta. Optimal cooking time, swelling index and water absorption index were affected by inclusion of fish powder. Addition of fish powder increases firmness and tensile strength of pasta.